PP.09.27: GENETIC ABNORMALITIES IN LATERALIZED MULTINODULAR PRIMARY ALDOSTERONISM. (June 2015) - Fernandes-Rosa, F.; Giscos-Duriez, I.; Amar, L.; Meatchi, T.; Boulkroun, S.; Zennaro, M.C.
Abstract : Objective: Primary aldosteronism (PA) is the most common form of secondary hypertension. Somatic mutations in the KCNJ5, ATP1A1, ATP2B3 and CACNA1D genes have recently been described in aldosterone-producing adenoma (APA). In addition, adrenals with APA show increased nodulation and cortical remodeling with zona glomerulosa hyperplasia. Although the functional link between somatic mutations and aldosterone production is clearly established, it is still not clear whether and how mutations lead to increased proliferation and nodulation. To verify if the somatic mutations are responsible for the entire adrenal phenotype (nodulation and aldosterone production) or isolated events occurring in a previously altered adrenal gland, the aim of this study was to investigate the presence of somatic KCNJ5, ATP1A1, ATP2B3 and CACNA1D mutations in secondary functional nodules of adrenals with APA. Design and method: We performed aldosterone synthase immunohistochemistry in multinodular adrenals to assess the functional characteristics of the secondary nodules for aldosterone secretion, followed by DNA extraction from functional secondary nodules from FFPE. Results: KCNJ5, ATP1A1, ATP2B3 and CACNA1D sequencing was performed on 33 functional secondary nodules from 26 multinodular adrenals of PA patients, collected through the COMETE network. In 12 adrenals, 4 harboring a somatic mutation in the APA and 8 without mutation in known genes, we identified the same mutation status between the APA and the secondary nodule. In 10 adrenals with the APA harboring a mutation, no mutations were identified in the secondary nodule. In 2 adrenals without mutation in APA, we identified a KCNJ5 mutation in the secondary nodule. In 1 adrenal harboring a KCNJ5 mutation in the APA, we identified the same mutation in two secondary nodules but no mutation was identified in a third secondary nodule. Finally, in 1 adrenal a CACNA1D mutation was identified in the APA and a KCNJ5 mutation in the secondary nodule. Conclusions: The identification of a different mutation status between APA and secondary nodules in the same adrenal suggests that somatic mutations found in APA are independent events leading to increased aldosterone production. The sequence of events underlying formation of aldosterone producing nodules remains to be elucidated.